Longitudinal case study of the role of libero in volleyball - Marra, F.; Aquino, M.; Altavilla, G. (Journal of Human Sport & Exercise, 2019)
In volleyball, the role of libero is highly specialized compared to the others, thanks to high abilities in the individual fundamental of the Bagher and in the team fundamentals of reception and defence. Therefore, coaches are committed to differentiate training programs from those of the remaining team members and this also affects the checks: in fact, results will have a greater weight compared to the same efficacy measurements of the fundamental of the Bagher of other roles. It`s therefore very useful to monitor, through a series of tests, the work done in the gym: results will help to recalibrate the training plan to combine team goals with needs of the libero. The purpose of this study is to monitor the level of efficacy of the individual fundamental of the Bagher, employed in the following moments of game: free-ball; service receiving; spike defence. To do this, the tests were: Bagher of free-ball in zone 5; receiving Bagher in zone 1 and in zone 6; defence Bagher in zone 5. The method is experimental longitudinal and consists in detecting the initial and final data in a period of time of 8 months for the technical ability in the aforementioned fundamental of a player in the role of libero in series B1. From the results, it comes out that the training activities are constantly monitored and the purpose can be considered achieved, because the coach has verified the athlete's performance level over time noting a final performance improvement, also confirmed by the game-data.